The influence of the notches on the natural frequencies - Dekýš V.; Kopas P.; Mazúr J.; Malcho M. (Applied and Computational Mechanics, 2007)
The simplification of the FEM model (the missing of a notch or a crack) generally means the modification of the natural frequencies. An analysis of these changes is matter of this paper. The direct and semicircle notches were made on the testing specimens (by cut depth in the specimens) and the naturals frequencies were measured and computed. The results are compared.In the paper is discussed the choice of the FEM element for FEM model and the comparison with experiment is made too.The influence of the crack on the natural frequencies is discussed in the case of specimen for high cycle fatigue test. The changes of the first three frequencies are compared for specimens with and without crack.